Quantification of D-dimer using a new fully automated assay: its application for the diagnosis of deep vein thrombosis - P Villa; F Ferrando; J Serra; H Faus; Y Mira; A Vaya; J Aznar (Haematologica, 2000)
BACKGROUND AND OBJECTIVE: A D-dimer assay can be helpful to rule out thromboembolism provided it is sensitive, reliable, fast and easy to perform. Tests based on the ELISA methodology have a high diagnostic sensitivity, and are therefore adequate for excluding deep venous thrombosis (DVT). The drawbacks are their long assay times, unsuitability to be run on single samples and cost. New methods have been developed, based either on the same principle, by immunofiltration or by microlatex immunoturbidimetric assays which seem to reach the high sensitivity and negative predictive value (NPV) required, but allowing fast and quantitative single sample analysis. The aim of this work was to evaluate one rapid test, a fully automated quantitative assay (IL Test D-dimer, run on an ACL 7000 coagulation analyzer, Instrumentation Laboratory). DESIGN AND METHODS: We compared the diagnostic value of IL Test for DVT with that of an ELISA (Dimertest Gold EIA Agen Biomedical Limited, Acacia Ridge, Australia). Eighty-six patients (43 men, 43 women, mean age: 61 years) showing DVT symptoms formed the population for this non-randomized controlled trial in a referral center. The diagnosis of DVT based on the clinical history, was confirmed by serial compression ultrasonography (CUS) with Doppler flow in 62 patients. RESULTS: The IL Test D-dimer proved to be rapid, automated and well suited for individual tests with a good reproducibility in three control plasmas with different concentrations of D-dimer (coefficient of variation range 0.54-3. 87%). Its performance was comparable to that of the Dimertest Gold EIA, as indicated by the areas under the receiver operating characteristic curves (Dimertest Gold EIA 0.748; IL Test D-dimer 0.70). On the basis of kappa coefficients, there was a good concordance between the Dimertest Gold EIA and IL Test D-dimer when the receiver operating characteristic (ROC) curves suggested cut-offs were used. The sensitivity (98.3%) and NPV (88.9%) shown by IL Test D-dimer are comparable or even better than those obtained for EIA (95%, 80%, respectively). INTERPRETATION AND CONCLUSIONS: This study shows that the new method can be included in prospective clinical trials to test the utility of D-dimer measurement in combination with other non-invasive diagnostic procedures in the management of DVT diagnosis.